Jejak Efisiensi Transmisi Kebijakan Moneter Berganda Di Indonesia - Khairunnisa, Arista; Suryani, Mardian; Capriyanti, Orisa; Azis, Ismi; Oktasari, Orin (Politeknik Raflesia Press, 2024)
Abstrak—. This research explains the need for dual monetary policy transmission to support Islamic finance and improve the economy which seeks the development of dual monetary policy transmission in Indonesia from 2003 to 2023 using a type of literature research. The results of research conducted from 2003 to 2023 found that monetary policy transmission using the sharia system was more effective compared to the conventional system. However, there is a sharia transmission route that has a negative value in economic growth, namely the profit sharing route. So it is necessary for the central bank to make a policy to handle the SBIS fee itself without adopting SBI as a cyan in calculating profit sharing Keywords: Moneter Policy, dual system banking,